2020
DOI: 10.2196/19782
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use, Risk Awareness, and Demographic Characteristics Associated With Engagement in Preventive Behaviors and Testing: Cross-Sectional Survey on COVID-19 in the United States

Abstract: Background During the coronavirus disease (COVID-19) pandemic, engagement in preventive behaviors and getting tested for the virus play a crucial role in protecting people from contracting the new coronavirus. Objective This study aims to examine how internet use, risk awareness, and demographic characteristics are associated with engagement in preventative behaviors and testing during the COVID-19 pandemic in the United States. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
172
7
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(220 citation statements)
references
References 30 publications
31
172
7
5
Order By: Relevance
“…Thus the measure appears to be valid across gender and political party allowing for comparison of scores. Our findings of higher positive and lower negative social distance attitudes among female compared to male respondents is consistent with other recent studies reporting gender differences in COVID-19 attitudes and practices [ [21] , [22] , [23] , 25 , 26 ]. Our finding of an association between political affiliation and both positive and negative social distance attitudes continues a troubling pattern that suggests partisan influence on attitudes and behaviors related to COVID-19 [ 22 , 23 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus the measure appears to be valid across gender and political party allowing for comparison of scores. Our findings of higher positive and lower negative social distance attitudes among female compared to male respondents is consistent with other recent studies reporting gender differences in COVID-19 attitudes and practices [ [21] , [22] , [23] , 25 , 26 ]. Our finding of an association between political affiliation and both positive and negative social distance attitudes continues a troubling pattern that suggests partisan influence on attitudes and behaviors related to COVID-19 [ 22 , 23 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is crucial to understand public attitudes towards social distancing. A growing body of work has examined knowledge, attitudes, and practices (KAPs) regarding COVID-19 [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. However, this work does not examine attitudes towards social distancing in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This study also revealed that the perceived sensitivity, perceived severity, perceived benefits, cues to action, and knowledge levels are substantial predictors accounting for the practice of prevention behaviors, which are in line with the previous literature [ 40 , 41 ]. It showed higher ORs for preventive behavior with perceived sensitivity; that is, people are more likely to take feasible preventive actions to avoid infection if there are confirmed cases in their community [ 7 ]. Another critical thing to note is that perceived barriers was a significant factor impeding the implementation of preventive behaviors, which is consistent with existing evidence [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous pandemics (such as SARS, MERS, etc. ), COVID-19 presents unprecedented challenges to the global public health response, in part, due to its unique epidemiological characteristics, the incubation period of COVID-19 can be up to 24 days [ 7 ]. The transmissibility might be higher for COVID-19 than for SARS, and the community spread is more prominent [ 8 ], which had led to more overall deaths due to the numerous cases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early indications suggest that this is the same finding for the current pandemic. In a study from China compared with males, females more frequently washed their hands (OR 2.39, 95% CI 1.85-3.09, P <.001) [42]. Other behavioral factors were also found in this study as women were more likely to: cover their nose and mouth when sneezing and coughing (OR 2.12, 95% CI 1.63-2.74, P < .001), keep social distance with others (OR 1.64, 95% CI 1.28-2.11, P < .001), stay home (OR 1.34, 95% CI 1.05-1.70, P = .02), avoid using public transportation (OR 2.30, 95% CI 1.72-3.07, P < .001), and clean frequently touched surfaces (OR 1.58, 95% CI 1.25-2.00, P < .001).…”
Section: Men's Health Behaviormentioning
confidence: 97%